Contextualized ubiquity: a new opportunity for rendering business information and services - Cunha, Carlos R. (2010)
Ubiquitous information and services means that they are available anywhere and anytime. The development of mobile-devices with wireless network-access capabilities, together with the decrease in network-traffic costs and the proliferation of free wireless hotspots, makes the use of mobile-devices, as Internet access tools, increasingly common and attractive. With novel forms of presenting information and to provide new ways to interact with consumers, new business strategies can be boost, in Customer Relationship Management (CRM) and E-Commerce. This paper describes a different approach to the relationship between customers and business-providers, based on contextualization mechanisms, located in user-consuming real-world objects. A Wine Integrated Management System, called SIGPV, is presented as a proof-of-concept, enumerating some of possible major business and CRM benefits.